Elaboración de un puré con propiedad funcionales a base de oca (Oxalis tuberosa) y pulpa de uvilla (Physalis peruviana) con efecto antioxidante y antimicrobiano - Arguello Ramírez, Martha Mercedes (2024)
The present research was conducted at the Research and Linkage Laboratory of the State University of Bolivar, whose main objective was: To elaborate a puree with functional properties based on oca pulp (Oxalis tuberosa) and uvilla pulp (Physalis peruviana) with antioxidant and antimicrobial effect, which are being lost due to lack of support to producers. For this purpose, the chemical composition, antioxidant content and antimicrobial activity of oca and uvilla were analyzed. The goose presented high percentages of fiber, ash, fat, °Brix, protein; the antimicrobial activity presented an inhibition halo of 22,66 mm in diameter against Pseudomona in the uvilla and the antioxidant activity presented a value of 2864,61 µmol ET/100 mL of sample. It was determined that the best sweetening time for the preparation of the puree was the mixture of treatment T1 (48 h of sweetened goose + 70 % goose + 30 % uvilla pulp), because it presented a value of 9,33 °Brix, which is within the parameters of the NTE INEN standard. In the prepared puree, the antioxidant content and antimicrobial activity were analyzed, where the T6 treatment (72 h of sweetened goose + 90 % goose + 10 % uvilla pulp) obtained a result of 3886,14 µmol ET/100 mL of antioxidant content sample, while the antimicrobial activity showed moderate inhibition halos for S. aureus, P. aeruginosa, E. coli and Salmonella bacteria. Finally, acceptability analysis was performed and T6 presented a higher percentage of acceptability in the parameters color, odor, flavor and consistency